Unbiased Modified Two-Parameter Estimator for the Linear Regression Model - Abidoye, A. O.; Ajayi, I. M.; Adewale, F. L.; Ogunjobi, J. O. (Journal of Scientific Research, 2022)
This study centers on estimating parameters in a linear regression model in the presence of multicollinearity. Multicollinearity poses a threat to the efficiency of the Ordinary Least Squares (OLS) estimator. Some alternative estimators have been developed as remedial measures to the earlier mentioned problem. This study introduces a new unbiased modified two-parameter estimator based on prior information. Its properties are also considered; the new estimator was compared with other estimators’ Mean Square Error (MSE). A numerical example and Monte Carlo simulation were used to illustrate the performance of the new estimator.